Diseño de automatización de la alineación y nivelación de rieles del proceso de soldadura aluminotérmica en la vía férrea de la empresa cerrejón (2022)
The main objective of this degree work is the design and automation of the rail alignment and leveling stage of the aluminothermic welding process carried out on the Cerrejón company railway. Methodologically, it was developed in three phases to fulfill the specific objectives: in the first, the rail alignment and leveling stages of the company's current process were analyzed, the second addresses the design and dynamic simulation of the alignment and leveling automation system. , finally the third presents the comparative analysis of the manual process versus the automated one